Increased von Willebrand factor over decreased ADAMTS‐13 activity is associated with poor prognosis in patients with advanced non‐small‐cell lung cancer. Issue 1 (4th April 2017) - Guo, Renyong; Yang, Jiezuan; Liu, Xia; Wu, Jianping; Chen, Yu
Abstract : Background: Hypercoagulability induced by the imbalance between von Willebrand factor (VWF) secretion and its cleaving protease (ADAMTS‐13) has been correlated with cancer metastasis. The aim of this study was to explore the prognostic significance of the VWF/ADAMTS‐13 ratio in advanced non‐small‐cell lung cancer (NSCLC). Methods: Pre‐treatment sera/plasma levels of VWF, ADAMTS‐13, VWF/ADAMTS‐13 ratio, factor (F) VIII, and other clinical/laboratory parameters were measured in 119 patients with advanced NSCLC and 102 healthy controls. All patients were followed up to determine the predictive value of these parameters for prognosis of advanced NSCLC. Results: Elevated VWF, VWF/ADAMTS‐13 ratio, and reduced ADAMTS‐13 were significantly correlated with the stage and grade of advanced NSCLC and the final status of disease ( P <.05). VWF levels and the VWF/ADAMTS‐13 ratio were also associated with response to chemotherapy ( P <.05). Multivariate analysis identified the VWF/ADAMTS‐13 ratio and D‐dimer as significant independent predictors of patient mortality. The area under the curve showed that the VWF/ADAMTS‐13 ratio was more useful than VWF, ADAMTS‐13, and D‐dimer to predict mortality. Kaplan‐Meier analysis showed that a low VWF/ADAMTS‐13 ratio was significantly predictive of improved survival ( P =.004). Conclusion: These results suggest that the imbalance between VWF secretion and ADAMTS‐13 may play a critical role in the hypercoagulability state in advanced NSCLC. Moreover, elevation of the plasma VWF/ADAMTS‐13 ratio may serve as an independent predictive factor for mortality in patients with advanced NSCLC.